2010
DOI: 10.1101/gad.586710
|View full text |Cite
|
Sign up to set email alerts
|

RNA methylation by Dnmt2 protects transfer RNAs against stress-induced cleavage

Abstract: Dnmt2 proteins are the most conserved members of the DNA methyltransferase enzyme family, but their substrate specificity and biological functions have been a subject of controversy. We show here that, in addition to tRNA Asp-GTC , tRNA Val-AAC and tRNA Gly-GCC are also methylated by Dnmt2. Drosophila Dnmt2 mutants showed reduced viability under stress conditions, and Dnmt2 relocalized to stress granules following heat shock. Strikingly, stress-induced cleavage of tRNAs was Dnmt2-dependent, and Dnmt2-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
691
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 634 publications
(710 citation statements)
references
References 31 publications
(47 reference statements)
13
691
1
5
Order By: Relevance
“…These observations indicate that the modification status of tRNA nucleotides can specifically target endonucleases. In addition, recent experiments in Drosophila showed that anticodon loop modification affects stressinduced endonuclease activities [18]. Specifically, cytosine-5-methylation at position C38 reduced the cleavage of specific tRNAs during the heat shock response (Fig.…”
Section: Trna Modifications Can Affect Trna Fragmentationmentioning
confidence: 93%
“…These observations indicate that the modification status of tRNA nucleotides can specifically target endonucleases. In addition, recent experiments in Drosophila showed that anticodon loop modification affects stressinduced endonuclease activities [18]. Specifically, cytosine-5-methylation at position C38 reduced the cleavage of specific tRNAs during the heat shock response (Fig.…”
Section: Trna Modifications Can Affect Trna Fragmentationmentioning
confidence: 93%
“…m 5 C modifications can be installed by any of the seven proteins of the Nol1/Nop2/SUN domain (NSUN) family and by an enzyme named DNA methyltransferase 2 (DNMT2). DNMT2 mainly catalyses the m 5 C modification in position 38 of tRNA Asp in human cells (Goll et al , 2006), while the so far characterised NSUN proteins show specificity for tRNAs (NSUN2, NSUN6; Schaefer et al , 2010; Tuorto et al , 2012; Blanco et al , 2014; Haag et al , 2015a) or rRNA (NSUN1/NOP2, NSUN5; Sloan et al , 2013; Tafforeau et al , 2013; Schosserer et al , 2015). NSUN2 can also modify vault RNAs and mRNAs (Hussain et al , 2013), and NSUN4 was described to localise to mitochondria where it was shown to methylate the mitochondrial 12S rRNA in mice (Cámara et al , 2011; Metodiev et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…No clear pattern of genomic cytosine methylation has been established by any study, and genomewide bisulfite sequencing studies of wild type Drosophila embryos at an average depth of 5.6-fold (Zemach et al 2010) and 32-fold (Raddatz et al 2013) did not report methylated cytosines. The finding that MT2 can methylate tRNAs has led to speculation that its primary function in Drosophila is RNA methylation (Goll et al 2006;Schaefer et al 2010;Durdevic et al 2013), and that genomic cytosine methylation is random and spurious (Schaefer and Lyko 2010b). The evidence that MT2 methylates RNAs does not demonstrate an absence of genomic cytosine methylation, which could be driven either by MT2 or by an unknown methyltransferase.…”
mentioning
confidence: 99%